THE EFFECT OF FINANCIAL PERFORMANCE AND COVID-19 ON STOCK RETURN OF TOURISM, HOTEL, AND RESTAURANT SUB-SECTORS COMPANY THAT LISTED ON INDONESIA STOCK EXCHANGE IN THE PERIOD OF Q2 2014 â Q4 2020 - Karina Nofyan, Syifa
Tourism is an important sector in Indonesia for economic growth and community empowerment. Since 2010, the tourism sector's contribution to Gross Domestic Product (GDP) has increased. The tourism sector's contribution to GDP in 2018 was 4.50 percent, but in 2019, it increased by 0.20 percent to 4.70 percent of GDP. The increased contribution of tourism to GDP was driven by an increase in the number of international and domestic tourists and investments. However, in 2020, the COVID-19 pandemic spread globally, making travelling difficult due to travel restrictions. This has significantly impacted the tourism industry, particularly tourism, hotel, and restaurant sub-sectors. As a result, this study was carried out to analyze the impact of financial performance and COVID-19 on stock return using selected financial ratios. ROE and EPS for Profitability Ratio, CR for Liquidity Ratio, TATO for Activity Ratio, DER for Solvency Ratio, and PER for Market Ratio. The data is based on financial reports published on the websites of 18 companies between Q2 2014 and Q4 2020. Purposive sampling was used to select the 18 companies. In this study, panel data regression with a Fixed Effect Model has been used. The analysis results show that ROE, CR, EPS, PER, and COVID-19 all impact stock returns. ROE, CR, EPS, and PER all significantly impact stock returns, whereas COVID-19 has a significant negative impact on stock returns. It also demonstrates that DER and TATO do not affect the stock returns of the 18 companies.